CAUSES AND EFFECTS OF LOWERING THE STANDARD OF LIVING IN UKRAINE - Stativka N.V.; Nadtochii A.O. (Pressing Problems of Public Administration, 2016)
The paper is devoted to challenges of providing decent living standards for the population as the basis for human potential preservation and development. The main causes of lowering the Ukrainian population’s living standards, the nature of its trends and eventual threats to the sustainable development of the national economy have been determined. Proposals for the living standards improvement by means of state policy have been substantiated.